MASA REFORMASI: ETATISASI HUKUM: Studi Atas Reformasi Hukum di Turki dan Mesir - Ahmad Zayyadi; Muhammad Fauzinudin Faiz (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2019)
This article is written as a review article with the aim of comprehensively understanding the history of reform—covering the periods of formalization, codification, legal reform, and the implementation of sharī‘ah in the Muslim world—and Turkey as a central reference for legal reform in Islamic societies, including Egypt and other regions. It also examines the historical processes and reform ideas of the nineteenth and early twentieth centuries, as well as their impacts on the development of law and legal institutions in Turkey (the Ottoman Empire) and Egypt. The main focus of this study is Turkey (Ottoman), with reference to Egypt, as these two countries represent the primary centers of legal reform whose influence eventually extended throughout the Muslim world.